Is clinical expertise a conflict of interest in research?. (October 2020) - Neill, Sara; Martin, Lisa; Harris, Lisa
Purpose: Doctors who research and provide abortion care have had their work characterized as a conflict of interest. We investigated whether surgeons who perform medical procedures other than abortion also routinely conduct research on that procedure and whether they disclose this as a relevant "conflict of interest." Method: We conducted a two-step literature review of five medical procedures—abortion, rhinoplasty, Mohs micrographic surgery, transurethral resection of the prostate, and laminectomy. We identified articles published between June 2011 and May 2012, and we calculated the proportion of articles authored by clinicians who also perform that procedure as well as the percentage that reported clinical care as a conflict of interest. We then screened conflict of interest statements on publications on said procedures from the same journals between 2012 and 2019 and calculated the proportion of publications that reported clinical work as a conflict of interest. Results: We identified 135 publications that met inclusion criteria. We calculated that 100% of publications on rhinoplasty, transurethral resection of the prostate, and Mohs included a clinician who performs that procedure. Seventy-five percent of publications on laminectomy and 78% of publications on abortion included a clinician. None of the reviewed research articles included a disclosure that the authors also performed the procedure. From 2012 to 2019, there were 1, 903 published articles on these procedures. None included a conflict of interest that disclosed clinical work as a conflict of interest. Conclusion: Although abortion providers publish as clinician-researchers at rates similar to surgeons in other areas of medicine, they alone face accusations that their clinical expertise is a potential conflict of interest. This stigmatizing practice could have wide-ranging consequences including delegitimization of the scientific method and peer review process broadly.